Public and private supply of beds and access to health care in the Covid-19 pandemic in Brazil - Costa, Danielle Conte Alves Riani (2022)
The COVID-19 pandemic, a global health crisis, has put health systems in several countries in check. In Brazil, patient care has brought about disparities in the offer and access to public and private services and initiatives to preserve healthcare segmentation. The work systematizes information about: beds for hospitalization by COVID-19; patients´  complaints claiming access; and initiatives to expand the offer of assistance resources involving government proposals and the private sector (health plans and hospitals). There was an expansion of hospital beds, but the uneven distribution in the regions of the country has not changed. Nor does it appear to have changed the pattern of rationed coverage on the part of health insurance companies. A considerable part of the analyzed lawsuits refers to the denial of access to clients of private plans due to contractual deficiency, while SUS patients requested place in the ICU. Lives were lost due to the absence of an effective protection regulation for both SUS patients and restrictive plans. Public intensive care units had maximum occupancy, while the private sector registered idle beds. The analysis shows barriers to access beds and resistance to attempts to unify public and private efforts to mitigate lethality by the new coronavirus.